Penerapan Karakter Religius Peserta Didik Melalui Metode Pembiasaan di SDIT Al Irsyad Al Islamiyyah Karawang - Dewi Solihat; Astuti Darmiyanti; Ferianto Ferianto (At-Ta'lim : Media Informasi Pendidikan Islam, 2022)
Abstract: Implementation of Religius Character of Students Through the Habituation Method at SDIT Al Irsyad Al Islamiyyah Karawang The implementation of character education for students has many challenges, one of which is resistance from the students themselves as well as the lack of exemplary educators. Efforts are made through habituation methods through school programs and supervised implementation by teachers. This study aims to describe the teacher's efforts to shape the religius character of students at SDIT Al Irsyad Al Islamiyyah Karawang through the habituation method. The approach in this study uses a qualitative descriptive approach. The subjects of this research are teachers and students. Methods of data collection using the method of observation, interviews, and documentation. The data analysis technique uses interactive analysis with data reduction, data presentation, and conclusion drawing steps. The results of the study show that the teacher's efforts in forming religius character through habituation methods include the habituation of smiles, greetings, and salim (3S), the habit of reading daily prayers, the habit of worshiping, the habit of reading the Koran and the habit of living clean and healthy. The supporting factors in the formation of the religius character of students are parents, all school members and adequate facilities and infrastructure.